1994
DOI: 10.1095/biolreprod50.2.449
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of the Interleukin-1 System in the Mouse Ovary during Follicular Growth, Ovulation, and Luteinization1

Abstract: The distribution of immunoreactive interleukin-1 receptor type I (IL-1R tI), IL-1 alpha, and IL-1 beta, and of macrophages, was investigated immunohistochemically in the mouse ovary during follicular growth, ovulation, and luteinization. For this purpose, an indirect immunofluorescence technique, using specific monoclonal antibodies against mouse IL-1R tI, mouse IL-1 alpha, IL-1 beta, and macrophage antigens (CD11b/CD18) was used with sections of paraffin-embedded ovaries from eCG and eCG/hCG-treated 12-wk-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(62 citation statements)
references
References 33 publications
(43 reference statements)
6
56
0
Order By: Relevance
“…The ovulatory process could be considered as an inflammatory reaction [7], and leukocytes, especially neutrophils and monocytes/macrophages, have been shown to infiltrate the ovaries just before ovulation [2,5,8]. It has been suggested that IL-1β derived from infiltrating leukocytes enhanced ovulation [3,10,20,21]. Therefore, IL-1β is indicated to begin to appear in serum of dairy cattle at around artificial insemination, probably at ovulation, and to persist at higher level during pregnancy and to decline serum IL-1β on day 3 was significantly higher than that in colostrum fed to newborns with no detectable serum IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…The ovulatory process could be considered as an inflammatory reaction [7], and leukocytes, especially neutrophils and monocytes/macrophages, have been shown to infiltrate the ovaries just before ovulation [2,5,8]. It has been suggested that IL-1β derived from infiltrating leukocytes enhanced ovulation [3,10,20,21]. Therefore, IL-1β is indicated to begin to appear in serum of dairy cattle at around artificial insemination, probably at ovulation, and to persist at higher level during pregnancy and to decline serum IL-1β on day 3 was significantly higher than that in colostrum fed to newborns with no detectable serum IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Although macrophages were not removed from our cell preparations it is unlikely that local IL-1 production could be attributed to these cells. In the pre-ovulatory ovary from different species, white blood cells are located in the medulla or theca layer, but are not usually detectable in granulosa until ovulation (26,27). Our study was carried out on rabbit pre-ovulatory follicles.…”
Section: Cells (6 7) Moreover Hurwitz Et Al (5) Observed In Vivomentioning
confidence: 99%
“…Several studies have demonstrated the constitutive expression of TNF, IL-1b, and their receptors in the thymus and ovary [37][38][39][40][41][42] and we could speculate a role of these cytokines in maintaining the constitutive expression of Tsg-5 observed in these organs. Therefore, we used TNF- 43 and TNFRSF1A-deficient 44 mice to investigate their role in regulation of constitutive expression of Tsg-5 gene.…”
Section: Tsg-5: a New Tnf-stimulated Gene Ef Abrantes Et Almentioning
confidence: 84%